Characterization of antimicrobial-resistant Staphylococcus aureus from retail foods in Beijing, China. (February 2021) - Li, Heng; Tang, Taya; Stegger, Marc; Dalsgaard, Anders; Liu, Tianlong; Leisner, Jørgen J.
Abstract: Staphylococcus aureus is an opportunistic pathogen leading to food poisoning as well as human infections. The present study examined the prevalence and characterization of antimicrobial-resistant S. aureus in sushi from 42 outlets and in pork products from eight outlets in Beijing, China. The total bacterial counts were between 3.0 and 8.9 log CFU/g (mean 5.5 ± 1.5 log CFU/g) in sushi products and 4.8 to 7.4 log CFU/g (mean 5.6 ± 0.8 log CFU/g) in pork products. The mean counts of coliforms were 2.7 and 2.9 log CFU/g in sushi and pork, respectively. Staphylococcus aureus was isolated from seven sushi outlets (13 isolates) and two pork outlets (2 isolates) with average counts below 2 log CFU/g in all cases. A total of 15 S. aureus isolates were further characterized. Six lineages of S. aureus were present, including ST398 (n = 5), ST25 (n = 4), ST15 (n = 2), ST59 (n = 2), ST8 (n = 1) and ST2631 (n = 1). Thirteen isolates contained the scn virulence marker, whereas four and eight isolates contained the virulence marker edinB and enterotoxin genes, respectively. Characterization of antimicrobial resistance profiles documented resistances to ampicillin (n = 15), penicillin (n = 14), ceftazidime (n = 6), erythromycin (n = 4), tetracycline (n = 3), clindamycin (n = 3), and gentamicin (n = 1). Three MRSA isolates were obtained, one from pork (ST398) and two from one sushi outlet (ST59). They were all resistant to at least three classes of antimicrobials and two of them contained the scn gene and enterotoxin genes. Twelve sushi isolates and one of the pork isolates contained the scn gene, indicating that they were of human origin. This emphasizes the potential importance of transmission through foods of antimicrobial-resistant S. aureus including MRSA. We also showed that S. aureus exhibited geographical variation with regards to ST profiles, antimicrobial-resistance and virulence genes when comparing isolates from sushi products sold in Beijing and Copenhagen, Denmark. Whereas food safety is not compromised by the presence of low amounts of S. aureus in sushi, this study shows that with regards to public health such foods may serve as vehicles for transmission of multidrug-resistant S. aureus and MRSA lineages. Highlights: The aerobic mesophilic counts were 5.5 ± 1.5 log CFU/g for sushi products and 5.6 ± 0.8 log CFU/g for pork products. Three MRSA strains were resistant to at least three classes of antimicrobials and thus designated as multidrug-resistant. Six lineages of S. aureus were detected: ST398 (n = 5), ST25 (n = 4), ST15 (n = 2), ST59 (n = 2), ST8 (n = 1) and ST2631 (n = 1). The MRSA isolates contained scn and enterotoxin genes.